Mineral phosphate solubilization by Pseudomonas aeruginosa isolates from chilli (Capsicum annuum L.) fields - Linu, M.S.; Sreekumar, J; Asok, Aju K.; Jisha, M.S. (Journal of Tropical Agriculture, 2018)
Phosphorus (P) is the second imperative key element after nitrogen as a mineral nutrient in terms of quantitative plant requirement. An adequate supply of P is obligatory for proper execution of various metabolic activities of plants. Identification of a potent phosphate solubilizing microorganism capable of transforming insoluble P into soluble and plant accessible forms is considered as the best eco-friendly option for providing inexpensive P to plants. In this study 12 phosphate solubilizing microorganisms were isolated from chilli rhizosphere by enrichment culture technique. P solubilisation efficiency was checked using vanadomolybdate phosphoric yellow colour method and two most efficient isolates, PS 2 and PS 3, were selected. Various parameters such as pH, temperature of incubation, carbon source, nitrogen source, NaCl concentration and incubation time were optimized for the selected isolates, Pseudomonas aeruginosa PS 2 (KR270346) and Pseudomonas aeruginosa PS 3 (KR270347). Maximum P solubilization rate was shown at pH 7, temperature 30°C and after 15 days of incubation. Glucose and ammonium sulphate were the best carbon and nitrogen sources for the selected isolates. Mineral phosphate solubilization was directly related to a pH drop in the culture medium. Production of gluconic acid by Pseudomonas aeruginosa during phosphate solubilization was confirmed by analyzing the culture medium by high performance liquid chromatography. The growth stimulation effect of selected isolates was confirmed by the vigour index determination and the treated rice seeds showed better germination percentage than control seeds.